DIPG-34. A HUMAN NEURAL STEM CELL DIPG MODEL IDENTIFIES THE RELATIVE CONTRIBUTION OF DIFFERENT ONCOGENIC ELEMENTS TO INVASIVE MALIGNANT TRANSFORMATION. Issue 2 (22nd June 2018) - Park, Youngran; An, Ping; Ding, Dacheng; Eberhart, Charles G; Raabe, Eric H
Abstract: Nearly 80% of Diffuse Intrinsic Pontine Glioma (DIPG) harbor H3K27M mutation which is inversely correlated with reduced survival, and 60% of H3K27M mutant cells are associated with TP53 mutation. However, it is unclear how those mutations interact to drive DIPG. To address the relative contributions, we added oncogenic elements that are known to present in DIPG in a stepwise fashion to hindbrain-derived hNSCs. These include the stem cell factor BMI1, p53 R248W, H3K27M, constitutively active AKT and hTERT. First, we found that the combination of BMI1 along with p53 R248W and hTERT could immortalize neural stem cells, but was insufficient to form tumors in vivo . Addition of activated AKT led to aggressive glial phenotype tumors in the pons of immunodeficient mice, but was not invasive as DIPG. Finally, the introduction of H3K27M mutation increases the invasion ability of transformed cells. We also found that H3K27M mutation increases expression of LIN28B, a stem cell factor, which might be implicated in invasion and tumorigenicity, suggesting that H3K27M mutation might facilitate invasiveness of DIPG through LIN28B and its downstream effectors HMGA2, SNAI1, and SLUG. In summary, we have developed a human hindbrain neural stem cell DIPG model which has both accurate cell of origin and genetic alterations. Our models allow for assessment of the relative contribution to transformation of each genetic element in a stepwise fashion in the likely cell of origin of this deadly tumor.